Here comes the fun: Mapping the journey from experience to loyalty in music festivals - Ambalika, Ni Komang Ayu Diah; Wiwekananda, I Gusti Ngurah Ary; Ditha, I Gusti Ayu Tara Laksemiyasa; Sawitri, Ni Luh Putu Widya (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Music festivals have become complex experiential platforms that generate not only entertainment but also social, cultural, and emotional engagement. This study investigates the journey from music festival experience quality to loyalty and focusing on the role of festival satisfaction and image. This research employed a quantitative method using an online survey that was distributed to music festival attendees in Indonesia. A total of 381 the collected valid responses were examined through Structural Equation Modeling (SEM-PLS). The findings showed that festival experience quality has a significant positive effect on festival satisfaction and festival image. Moreover, festival satisfaction enhances both festival image and festival loyalty, while the festival image further strengthens festival loyalty. These results indicate that bringing high-quality experiences, fostering satisfaction, and cultivating a strong festival image are crucial strategies for building loyalty. From the managerial perspective, the study also focuses on the dominant student segment by tailoring music festival concept or design and creating marketing strategies to their preferences. Nevertheless this study is limited by its diverse festival contexts making the future studies are recommended to investigate specific or single type of music festivals, distinguish between the first-time and repeat visitors.